Direct and simultaneous determination of Cd, Cu, and Se in blood samples by graphite furnace atomic absorption spectrometry - Caldas, Naise Mary; Raposo, Jorge Luiz [UNESP]; Oliveira, Silvana Ruella [UNESP]; Neto, José Anchieta Gomes [UNESP]; Barbosa, Fernando (My University, 2009)
A graphite furnace atomic absorption speclromclric method is proposed for the direct and simultaneous determination of Cd. Cu. and Se in human blood. Samples were diluted 1:10 (v/v) in 0.6% (v/v) UNO3 + 0.6% (v/v) Triton X-100 solution. Tor 12 μL injected sample volume + 6 μL of 1000 mg L-1 Pd(NO3)2+ 3 μL of 1000 mg L-1 Mg(NO3)2. the calculated characteristic masses (mo) were 0.9 pg Cd. 16 pg Cu. and 39 pg Se. which are close to those mo values for single-element conditions for THGA furnace (1.3 pg Cd, 17 pg Cu. and 16 pg Se). Calibration curves with linear correlations better than 0.999 were obtained. The limits of detection (LOD) were 0.03 μg L-1 Cd, 0.075 μg L -1 Cu and 0.3 μg L-1 Se, and the relative standard deviations (n= 12) were 2.6%. 0.3%. and 1.6%. respectively. The method was applied for Cd, Cu, and Se determination in 10 human blood samples and the results were in agreement at the 96% confidence level with those obtained by inductively coupled plasma mass spectrometry. Concentrations of analytes in the selected blood samples varied from 1.7 to 3.2 μg L-1 Cd. 700 to 921.7 μg L-1 Cu. and from 68.6 to 360 μg L-1 Se. The accuracy of the proposed method was also evaluated by an additionrecovery experiment and recoveries of Cd, Cu, and Se added to blood samples ranged from 99-109%. 91-103%. and 93-103%. respectively.